Anti-hydroxy-3-methylglutaryl-coenzyme A reductase (anti-HMGCR) antibody in necrotizing myopathy: treatment outcomes, cancer risk, and role of autoantibody level. (2nd September 2020) - Aggarwal, R; Moghadam-Kia, S; Lacomis, D; Malik, A; Qi, Z; Koontz, D; Burlingame, RW; Oddis, CV
Abstract : Objective : To evaluate clinical associations of anti-hydroxy-3-methylglutaryl-coenzyme A reductase (anti-HMGCR) antibody (Ab) and statin exposure in necrotizing myopathy (NM) patients. Methods : NM without a known myositis-specific autoantibody (MSA) was ascertained from a large single-centre myositis database between 1985 and 2012. A comparison NM cohort included 32 anti-SRP + autoantibody patients, and other control groups included 74 non-NM myositis patients and 21 non-myositis controls. Sera from all cases and controls were tested using a validated anti-HMGCR enzyme-linked immunosorbent assay. Clinical features including statin use and anti-HMGCR Ab status were compared between cases and controls. Results : Of the 256 NM muscle biopsies reviewed, only 48 subjects with available sera were identified as traditional MSA-negative NM. Anti-HMGCR positivity was significantly (p < 0.001) associated with MSA-negative NM [48% (23/48)] compared to all of the myositis and non-myositis controls [5% (6/127)]. Most anti-HMGCR Ab-positive NM patients had high titres of anti-HMGCR (83%) and a history of statin exposure (78%), along with severe muscle weakness, high creatine kinase (CK) levels (90% ≥ 5000 IU/L), a paucity of other organ manifestations, and the need for immunosuppression with prednisone and methotrexate, but generally favourable outcomes. Anti-HMGCR serum levels were associated with baseline CK levels but not muscle weakness. Conclusion : HMGCR Ab-positive NM patients are associated with statin exposure, have severe muscle weakness and high CK at presentation, lack other organ manifestations, and generally have favourable outcomes from immunosuppression. Anti-HMGCR Abs should be assessed in MSA-negative NM patients, particularly those with a history of statin exposure.